ART THERAPY AS CHILDREN TRAUMA HEALING POST-DISASTER OF MOUNT SEMERU - Winda Amilia; Ahmad Yusuf; Anfaq Syahriyal Fadhil; Anindya Dyah Untari; Irmy Arya Tri Nasrin; Mohammad Nor; Andrew Setiawan Rusdianto (UPT Penerbitan Universitas Jember, 2022)
Disasters are natural events that disrupt and threaten human life. The eruption of Mount Semeru in December 2021 was one of the natural disasters that caused tremendous damage. Children and adolescents are more vulnerable to psychological manifestations related to disasters. Handling of children's trauma needs to be done because children do not have the capacity to look after and care for themselves. The behavior of children who were victims of the eruption of Mount Semeru before intervention tended to show a passive and restless attitude. Art therapy is an effective intervention to increase self-esteem. The forms of art therapy given to children affected by the eruption of Mount Semeru are drawing, group storytelling, making crafts, and writing and reading poetry. The methods used in trauma healing with art therapy are mentoring and training. As a result of art therapy activities, children are able to express what they feel during a disaster and are able to convey hope in the future. Keywords: disaster, PTSD, drawing, story telling, bibliotherapy